REVIEW OF MODERN SYSTEMS FOR THE PROTECTION OF ELECTRONIC SERVICES - KOVALEVSKYI , VIACHESLAV; VAKALIUK, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The use of electronic services is an integral part of modern life. Various electronic services transmit and process vast volumes of user data. Users of these services must be assured that all interactions with their data are conducted in compliance with modern security standards and prevent unauthorized access. This article reviews the existing modern protection systems that can be implemented to establish a multi-level security system for electronic services. The analysis indicates that machine learning technologies and the automation of threat detection and prevention processes play a significant role in the construction of modern electronic service protection systems. This approach reduces the response time to threats, minimizes the impact of human factors, and enables the construction of security systems that can be quickly scaled depending on the tasks. It is evident that traditional data protection systems, including data encryption systems and network firewalls, retain their relevance in the context of electronic services. Furthermore, the contribution of major technology companies to the security industry should be noted. By providing services for hosting electronic services, data transmission, and processing, these companies gain access to a significant amount of user traffic, enabling them to analyze it for security risks. Additionally, there is ongoing work to improve existing and develop new protection systems for electronic services, taking into account modern security demands. Given the significant impact of the implementation and use of electronic services in the global economy, the economic consequences of security incidents remain a crucial topic of discussion at international economic conferences, both in the context of individual companies and countries as a whole.